2010
DOI: 10.1371/journal.pone.0015534
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of FGF-21 Are Increased in Coronary Heart Disease Patients and Are Independently Associated with Adverse Lipid Profile

Abstract: BackgroundFibroblast growth factor 21 (FGF-21) is a metabolic regulator with multiple beneficial effects on glucose homeostasis and lipid metabolism in animal models. The relationship between plasma levels of FGF-21 and coronary heart disease (CHD) in unknown.Methodology/Principal FindingsThis study aimed to investigate the correlation of serum FGF-21 levels and lipid metabolism in the patients with coronary heart disease. We performed a logistic regression analysis of the relation between serum levels of FGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
132
3
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 29 publications
9
132
3
4
Order By: Relevance
“…Based on our in vitro studies showing that FGF21 protects against palmitate-induced cardiac apoptosis in H9c2 cells and primary cardiomyocytes, and also previous reports indicating that liver-and adipose-tissue-secreted FGF21 protects the heart from ischaemia/reperfusion injury [18] and exogenous FGF21 protects the heart from isoprenaline-induced cardiac hypertrophy [20], we presume that cardiac protection from diabetes by FGF21 may predominantly be attributed to its direct actions on the heart. The present study elucidated the intracellular mechanisms by which FGF21 prevents palmitate-mediated apoptosis in vitro and NEFA-infusion-or diabetes-mediated apoptosis [35][36][37]. Zhu et al revealed that FGF21 ameliorates BP in a fructoseinduced hypertension model [38].…”
Section: Discussionmentioning
confidence: 86%
“…Based on our in vitro studies showing that FGF21 protects against palmitate-induced cardiac apoptosis in H9c2 cells and primary cardiomyocytes, and also previous reports indicating that liver-and adipose-tissue-secreted FGF21 protects the heart from ischaemia/reperfusion injury [18] and exogenous FGF21 protects the heart from isoprenaline-induced cardiac hypertrophy [20], we presume that cardiac protection from diabetes by FGF21 may predominantly be attributed to its direct actions on the heart. The present study elucidated the intracellular mechanisms by which FGF21 prevents palmitate-mediated apoptosis in vitro and NEFA-infusion-or diabetes-mediated apoptosis [35][36][37]. Zhu et al revealed that FGF21 ameliorates BP in a fructoseinduced hypertension model [38].…”
Section: Discussionmentioning
confidence: 86%
“…Our findings have expanded the current understanding on the relationship between serum FGF21 and CHD. Several cross‐sectional studies had shown that serum FGF21 levels were significantly higher in subjects with CHD than those in controls 13, 14. In a study involving 100 Chinese subjects, with 38% of them having T2DM, serum FGF21 levels were independently associated with the presence of acute myocardial infarction and were significantly higher in those who developed reinfarction within 30 days 15.…”
Section: Discussionmentioning
confidence: 97%
“…Over the years, the association of circulating FGF21 with CHD in T2DM has not been clearly defined. In cross‐sectional studies, conflicting results were reported regarding circulating FGF21 levels in subjects with CHD, with an association of raised FGF21 levels with CHD reported in some studies,13, 14, 15 but not in others 16, 17. The association of circulating FGF21 with CHD in T2DM, especially among those without known cardiovascular disease (CVD), remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…FGF21 regulates peroxisome proliferator-activated receptor-γ (PPAR-γ ) and the glucose-l ow ering acti vi ty of thiazolidinediones [3,4]. Despite these beneficial effects of FGF21 in glucose metabolism in animal studies, circulating FGF21 levels are often elevated in obesity, dyslipidaemia, insulin resistance, type 2 diabetes and coronary artery disease [2,[5][6][7]. The elevation in FGF21 levels may be a compensatory response to underlying metabolic stress or may be due to impaired FGF21 signalling leading to FGF21 resistance [8].…”
Section: Introductionmentioning
confidence: 99%